Development of the Educational Game Scale - Cenan Isci,; Sedef Celik Demirci, (Journal of Educational Issues, 2024)
In recent years, the importance of educational games for students is increasing. Therefore, the points of view of students about educational games are among the issues that gain importance. In this study, a scale was developed that determines students’ perceptions of educational games. For this purpose, after a literature review, a 33-item question pool was created by a field specialist. The draft scale was prepared and applied to 445 students studying at secondary school, and after that exploratory and confirmatory factor analysis was applied to the obtained data. As a result of the exploratory factor analysis, 10 items collected under 2 factors explained 55.71% of the total variance. These factors were grouped as ‘mental adaptation’ and ‘physical adaptation’. The Cronbach-Alpha internal consistency coefficient of the scale, which was finalized by factor analysis, was found to be α = 0.90. These results show that the scale is valid and reliable. Analysis results show that the developed scale can be used to determine students’ perceptions about educational games.